Where have your time and space gone? An analysis of technology addiction, surveillance capitalism, and the modern panopticon - Matsui, Erika (Penerbit Universiti Kebangsaan Malaysia, 2021)
Little attention has been paid to why individuals are addicted to Internet-related experiences. This research identifies a key driver of technology addiction by combining three perspectives: behavioural science, economics, and psychoanalysis. Behavioural science reveals that technology addiction is produced by well-designed technology that fulfils humans’ fundamental needs. Capital economy analysis, called surveillance capitalism, offers a new interpretation of the data-driven economy, in which Internet technology enterprises collect feedback from users’ experiences and use said feedback to improve their products. The data accumulation logic facilitates automatic thinking and the modification of users’ behaviours to make a profit for the enterprises. Psychoanalysis clarifies the relationship between surveillance power and behavioural changes in society. The Panopticon, a central observation tower with a circle of prison cells, achieved an automatic function of power to control individuals’ performances and minds. Technology addiction is a symptom of the modern Panopticon because a common mechanism works between the Panopticon and surveillance capitalism, occupying individuals’ time and space and executing the automatic function of the surveillance power that facilitates behavioural modification. We conclude that depriving individuals of both time and space is a key driver of technology addiction that threatens sovereignty in a data-driven economy. We also provide three solutions to technology addiction: acknowledgement of the benefits and risks of technology use, acceptance of the complexity underlying technology-related issues, and protection of individual sovereignty.